Implementasi Peraturan Daerah Provinsi Sumatera Utara Nomor 1 Tahun 2019 Oleh Badan Kesatuan Bangsa Dan Politik Provinsi Sumatera Utara - Rosenna Sihaloho; Tengku Irmayanti; Hatta Ridho (Universitas Medan Area, 2023)
The purpose of this study was to identify and analyze the conditions of drug abuse and what factors influenced the implementation of Regional Regulation Number 1 of 2019 and the obstacles faced by the Provsu Kesbangpol Agency as the coordinator in implementing the facilitation policy for preventing drug abuse in North Sumatra. The approach used in this study is a qualitative approach. The results of the study found that the implementation of North Sumatra Province Regional Regulation No. 1 of 2019 concerning Facilitation of Drug Abuse Prevention by the National Unity and Political Agency of North Sumatra Province in 2020-2021 has not gone well. Utilization of resources that are not yet optimal because they are not supported by human resources and inadequate budget allocations; Lack of communication and coordination among implementing organizations; The commitment of the Provsu Kesbangpol Agency which is still not strong enough; External conditions, especially economic conditions and social conditions, do not support the implementation of Regional Regulation No. 1 of 2019 due to the Covid-19 pandemic. Constraints faced include: Not yet optimal resources both HR and Allocation; Lack of OPD support and commitment; District/city government support in North Sumatra is still low. Until now, there are still many district/city governments that do not have regional regulations; The Covid-19 pandemic that occurred in 2020 became an obstacle for the Kesbangpol Agency in implementing Regional Regulation Number 1 of 2019.